Effects of elemental segregation on microstructural evolution and local mechanical properties in a dynamically deformed CrMnFeCoNi high entropy alloy. (1st January 2021) - Hasan, M.N.; Gu, J.; Jiang, S.; Wang, H.J.; Cabral, M.; Ni, S.; An, X.H.; Song, M.; Shen, L.M.; Liao, X.Z.
Abstract: The effect of elemental segregation on local hardness and microstructural evolution introduced by high strain-rate deformation in a CrMnFeCoNi high entropy alloy was investigated. Mn and Ni elemental segregation to interdendritic boundaries occurs during the solidification process and is intensified by dynamic deformation. Local hardness is reduced in the Mn and Ni enriched areas, which may be due to the increase of local stacking fault energy that changes the deformation mechanisms. This leads to the alternation of soft and hard regions and the structure is effective in hindering the propagation of adiabatic shear bands that would toughen the material. Graphical abstract: Image, graphical abstract